2020
DOI: 10.1111/ijlh.13357
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemia with mutated NPM1 mimics acute promyelocytic leukemia presentation

Abstract: Objectives To investigate clinicopathological and molecular features of NPM1‐mutated acute myeloid leukemia that presented with infrequent acute promyelocytic leukemia (APL)‐like phenotype and clinical presentation. Methods Cases with both de novo or secondary Acute Myeloid Leukemia (AML) were retrieved. Data from flow cytometry immunophenotyping, cytogenetics, molecular studies, and clinical presentation were analyzed. Results Cases presented with abnormal coagulation parameters and low platelets count; four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…They also found that the leukaemic cell counts of bone marrow was higher in HLA-DR negative non-APL than in HLA-DR positive non-APL group. Similarly, Rosainz et al 22…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They also found that the leukaemic cell counts of bone marrow was higher in HLA-DR negative non-APL than in HLA-DR positive non-APL group. Similarly, Rosainz et al 22…”
Section: Discussionmentioning
confidence: 86%
“…They also found that the leukaemic cell counts of bone marrow was higher in HLA‐DR negative non‐APL than in HLA‐DR positive non‐APL group. Similarly, Rosainz et al 22 presented five cases of NPM1 mutated that exhibited APL‐like immunophenotypes and clinical presentation with deranged coagulation parameters which is frequently associated with APL. In comparison to these studies, we had subdivided the HLA‐DR negative AML group on the basis of CD34 expression and found that CD34 negative group was more associated with DIC with no significant expression of CD19 in both groups.…”
Section: Discussionmentioning
confidence: 95%
“…Dear Editors, In a recent article, Arana Rosainz et al 1 present the diagnostic challenges that may arise in the phenotyping of acute myeloid leukemia (AML) when CD34 is not expressed by the blastic population.…”
Section: E T T E R T O T H E E D I T O R On the Distinction Between A...mentioning
confidence: 99%
“…However, in some cases of AML with cytological characteristics closely resembling M3 or M3v FAB morphology, no RARA rearrangement can be detected. This group of RARA -negative AML with APL-like morphological features is either associated with other RAR family genes rearrangements such as RARB and RARG [ 2 ] or lacks any RAR rearrangements at all [ 5 , 15 ]. The diagnosis of these AML types is difficult, and therapy with all-trans retinoic acid (ATRA) and arsenic trioxide (ATO) is not effective due to the lack of specific drug binding sites [ 1 , 16 ].…”
Section: Introductionmentioning
confidence: 99%